2014
DOI: 10.1002/pat.3285
|View full text |Cite
|
Sign up to set email alerts
|

A new zwitterionic electrochromatographic stationary phase based on poly(3-chloro-2-hydroxypropyl methacrylate-co-ethylene dimethacrylate) reactive monolith

Abstract: A new reactive monolith, poly(3‐chloro‐2‐hydroxypropyl methacrylate‐co‐ethylene dimethacrylate), poly(HPMA‐Cl‐co‐EDMA) was synthesized and post‐functionalized by taurine (2‐aminoethane sulfonic acid) to obtain a zwitterionic stationary phase for capillary electrochromatography. The new stationary phase contained charged groups such as secondary amine providing anodic electroosmotic flow and sulfonic acid groups providing cathodic electroosmotic flow. Hence, the capillary electrochromatography separations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…see . Other monoliths have been described recently for postpolymerization modification, including monoliths based on glyceryl methacrylate (GMM) , N‐(3‐aminopropyl) methacrylamide hydrochloride (NAPM) , N‐acryloxysuccinamide , and 3‐chloro‐2‐hydroxypropyl methacrylate .…”
Section: Introductionmentioning
confidence: 99%
“…see . Other monoliths have been described recently for postpolymerization modification, including monoliths based on glyceryl methacrylate (GMM) , N‐(3‐aminopropyl) methacrylamide hydrochloride (NAPM) , N‐acryloxysuccinamide , and 3‐chloro‐2‐hydroxypropyl methacrylate .…”
Section: Introductionmentioning
confidence: 99%
“…Aydoğan et al. reported a new reactive PMC for the separation of nucleosides in CEC with anodic EOF . The monolith was prepared by an in‐situ copolymerization of 3‐chloro‐2‐hydroxypropyl methacrylate (HPMA‐Cl) as the monomer and EDMA as the crosslinker.…”
Section: Pmcs In Food Analysismentioning
confidence: 99%
“…The column exhibited a better separation performance and in turn, a good separation was observed for nucleobases, nucleosides, nucleotides, and small peptides on the poly(SPP-co-N,N'-methylene bisacrylamide) monolith when compared to the ZIC-HILIC column. Aydoğan et al reported a new reactive PMC for the separation of nucleosides in CEC with anodic EOF [47]. The monolith was prepared by an in-situ copolymerization of 3-chloro-2hydroxypropyl methacrylate (HPMA-Cl) as the monomer and EDMA as the crosslinker.…”
Section: Hilic With Polar Pmcsmentioning
confidence: 99%
“…34 In our reported studies, poly(HPMA-Cl-co-EDMA)-based capillary monoliths carrying anionic and zwitterionic ligands were firstly introduced to the literature in CEC. 35,36 These monolithic columns, however, displayed limited hydrophilicity 35 and mobile phases that use high amount of organic modifier (around 60% ACN) were used to achieve sufficient retention and selectivity for polar analytes. 36 Moreover, the separation of polar analytes including amides and phenols was mainly performed with ACN content exceeding 90% in the mobile phase to achieve sufficient retention.…”
mentioning
confidence: 99%
“…35,36 These monolithic columns, however, displayed limited hydrophilicity 35 and mobile phases that use high amount of organic modifier (around 60% ACN) were used to achieve sufficient retention and selectivity for polar analytes. 36 Moreover, the separation of polar analytes including amides and phenols was mainly performed with ACN content exceeding 90% in the mobile phase to achieve sufficient retention. 8,20,37 Since it consumed large volumes of organic solvents, it would be less friendly for the environment.…”
mentioning
confidence: 99%